Dynamic analysis of refrigerated truck integrated with combined cooling and power cycle under various driving conditions. (15th February 2023) - Yao, Yu; Shi, Lingfeng; He, Jintao; Tian, Hua; Wang, Xuan; Zhang, Xuanang; Sun, Xiaocun; Lu, Bowen; Shu, Gequn
Graphical abstract: Highlights: Vehicle model for refrigerated truck with combined cooling and power cycle is proposed. Dynamic analysis is carried out with road condition and carrying load as key factors. Cogeneration system realizes saving fuel, additional work, and cooling capacity. The design suggestions for operating control strategy are given. Abstract: Waste heat recovery via combined cooling and power cycle (CCP-WHR) has become a promising energy-saving solution for refrigerated trucks owing to its capability for miniaturization, high efficiency, and multi-load supply. To ensure safety, stability, and efficiency under transient driving conditions, CCP-WHR needs to be adapted and coordinated with the complex and extreme fluctuations in energy conversion and transmission of the engine, which are difficult to explore in existing steady-state research. In this study, we establish a dynamic vehicle model for a refrigerated truck with CCP-WHR that can accurately track the driving cycle and adjust the operating mode. The dynamic characteristics, including vehicular operational performance (engine speed, torque, and waste heat parameters) and CCP-WHR output benefits (net work and cooling capacity), are analyzed with driving and load-carrying conditions as critical operating parameters. The comprehensive energy-saving performance of the entire vehicle is evaluated based on the proposed indicators. A refrigerated truck equipped with CCP-WHR demonstrated high adaptability to highway, suburban, and synthetic road conditions. Apart from achieving a 10.0 kW cooling capacity without requiring additional fuel consumption, CCP-WHR achieved a fuel saving of 2.8 L/100 km (6.4 %), additional power generation of 9.1 kW (5.5 %), fuel economy improvement of 8.9 g/kWh (6.3 %), and carbon emission reduction of 73.9 g/km (−6.4 %) under highway and full-load conditions. The dynamic study of the entire vehicle with CCP-WHR has guiding significance for control strategies and engineering prototypes.